Bereaved family members' perceptions of the quality of end-of-life care across four types of inpatient care settings. Issue 1 (December 2017) - Stajduhar, Kelli; Sawatzky, Richard; Robin Cohen, S.; Heyland, Daren; Allan, Diane; Bidgood, Darcee; Norgrove, Leah; Gadermann, Anne
Abstract Background The aims of this study were to gain a better understanding of how bereaved family members perceive the quality of EOL care by comparing their satisfaction with quality of end-of-life care across four different settings and by additionally examining the extent to which demographic characteristics and psychological variables (resilience, optimism, grief) explain variation in satisfaction. Methods A cross-sectional mail-out survey was conducted of bereaved family members of patients who had died in extended care units (n  = 63), intensive care units (n  = 30), medical care units (n  = 140) and palliative care units (n  = 155). 1254 death records were screened and 712 bereaved family caregivers were identified as eligible, of which 558 (who were initially contacted by mail and then followed up by phone) agreed to receive a questionnaire and 388 returned a completed questionnaire (response rate of 70%). Measures included satisfaction with end-of-life care (CANHELP-Can adianH ealth CareE val uationP roject - family caregiver bereavement version; scores range from 0 = not at all satisfied to 5 = completely satisfied), grief (Texas Revised Inventory of Grief (TRIG)), optimism (Life Orientation Test – Revised) and resilience (The Resilience Scale). ANCOVA and multivariate linear regression were used to analyze the data. Results Family members experienced significantly lower satisfaction in MCU (mean = 3.69) relative to other settings (means of 3.90 [MCU], 4.14 [ICU], and 4.00 [PCU];F (3371) = 8.30, p  = .000). Statistically significant differences were also observed for CANHELP subscales of "doctor and nurse care", "illness management", "health services" and "communication". The regression model explained 18.9% of the variance in the CANHELP total scale, and between 11.8% and 27.8% of the variance in the subscales. Explained variance in the CANHELP total score was attributable to the setting of care and psychological characteristics of family members (44%), in particular resilience. Conclusion Findings suggest room for improvement across all settings of care, but improving quality in acute care and palliative care should be a priority. Resiliency appears to be an important psychological characteristic in influencing how family members appraise care quality and point to possible sites for targeted intervention.